Steady state boiling crisis in a helium vertically heated natural circulation loop – Part 1: Critical heat flux, boiling crisis onset and hysteresis. (January 2016) - Furci, H.; Baudouy, B.; Four, A.; Meuris, C.
Highlights: Experiments were conducted on a 4.2 K boiling helium natural circulation loop. CHF values were measured and compared to predictions from the literature. An anomalous violent CHF spatial extension was observed. The rewetting process is substantially different if the violent extension of CHF has occurred. Abstract: Experiments were conducted on a 2-m high two-phase helium natural circulation loop operating at 4.2 K and 1 atm. The same loop was used in two experiments with different heated section internal diameter (10 and 6 mm). The power applied on the heated section wall was controlled in increasing and decreasing sequences, and temperature along the section, mass flow rate and pressure drop evolutions were recorded. The values of critical heat flux (CHF) were found at different positions of the test section, and the post-CHF regime was studied. The predictions of CHF by existing correlations were good in the downstream portion of the section, however CHF anomalies have been observed near the entrance, in the low quality region. In resonance with this, the re-wetting of the surface has distinct hysteresis behavior in each of the two CHF regions. Furthermore, hydraulics effects of crisis, namely on friction, were studied (Part 2). This research is the starting point to future works addressing transients conducing to boiling crisis in helium natural circulation loops.